Djibouti Economic Monitor : Navigating through the Pandemic and Regional Tensions - World Bank (Washington, DC: World Bank, 2022)
Severely impacted by the Coronavirus (COVID-19) pandemic in 2020, Djibouti’s economic activity has shown signs of recovery in 2021.This first edition of the Djibouti Economic Monitor (DEM) launches a program of reports with semi-annual frequency that analyze the trends and constraints to Djibouti’s development. Each issue will provide an update of recent economic developments (Chapter 1) and present the outlook as forecast by World Bank Staff together with key risks surrounding the outlook (Chapter 2). In addition, the DEM will also include a Special Focus section where we will delve in more depth on a topic of interest to the public. The Special Focus of the first issue of the DEM discusses the impact of the COVID-19 on the labor market and household welfare (Chapter 3).